2020
DOI: 10.1002/nau.24491
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gestational diabetes on pelvic floor: A prospective cohort study with three‐dimensional ultrasound during two‐time points in pregnancy

Abstract: Aim: To evaluate the pelvic floor (PF) biometry using three-dimensional ultrasound (US) at two-time points of gestational in pregnant women with gestational diabetes mellitus (GDM). Methods: A prospective cohort study conducted at the Perinatal Diabetes Research Center including 44 pregnant women with GDM and 66 pregnant women without GDM at 24 to 28 weeks of gestation. Three-dimensional transperineal US was performed at 24 to 28 and 34 to 38 weeks of gestation in the lithotomy position at rest. The axial plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Indeed, higher UI prevalence and severity have been associated with hyperglycemic disturbances not only during pregnancy ( 2 , 3 , 37 ) but also on prediabetes and clinical diabetes ( 38 , 39 ). Three-dimensional ultrasonography during rest showed that there is a decrement of the thickness of the levator ani muscle ( 17 ) during pregnancy, which is consistent with previous morphological findings of a myopathic process on musculoskeletal tissue of GDM pregnant women ( 6 , 15 ). However, conclusive evidence to support this relationship has not yet been assessed due to the lack of studies assessing pelvic floor function by direct measures ( 40 42 ), particularly on pregnancy until medium and long-term postpartum ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Indeed, higher UI prevalence and severity have been associated with hyperglycemic disturbances not only during pregnancy ( 2 , 3 , 37 ) but also on prediabetes and clinical diabetes ( 38 , 39 ). Three-dimensional ultrasonography during rest showed that there is a decrement of the thickness of the levator ani muscle ( 17 ) during pregnancy, which is consistent with previous morphological findings of a myopathic process on musculoskeletal tissue of GDM pregnant women ( 6 , 15 ). However, conclusive evidence to support this relationship has not yet been assessed due to the lack of studies assessing pelvic floor function by direct measures ( 40 42 ), particularly on pregnancy until medium and long-term postpartum ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Experimental studies in moderate diabetic rat models have shown that the periurethral and rectus abdominis muscles present deterioration, such as atrophy, thinning, disorganization, and co-localization of fast and slow fibers ( 7 , 8 , 10 , 14 ). These data are consistent with those observed in rectus abdominis muscle tissues collected from pregnant women with GDM during C-section ( 6 , 15 ), which suggests that GDM is indeed capable of damaging the muscular tissue causing a myopathic process ( 6 , 15 17 ). Establishing a rational line by the morphological findings from urethral and rectus abdominis muscle of rats ( 7 , 8 , 10 , 14 ) and rectus abdominis on pregnant women ( 6 , 15 ), the PFM is also potentially impacted by the myopathic process ( 6 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Women with GDM have an increased risk of urinary incontinence (UI) within the first decade after delivery when compared to non‐GDM women 2–4 . Furthermore, GDM is linked to a muscle injury that weakens the pelvic floor muscle (PFM) and rectus abdominis muscles (RAM) during pregnancy 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Furthermore, GDM is linked to a muscle injury that weakens the pelvic floor muscle (PFM) and rectus abdominis muscles (RAM) during pregnancy. [5][6][7][8] According to translational research, the PFM and RAM of pregnant diabetic rats demonstrate atrophy, colocalization of fast and slow fibers, an increased collagen type I/III ratio, and a decrease in total glycosaminoglycan. 9 These major findings from the literature review on hyperglycemia in pregnant rats and PFM and/or RAM myopathy prompted us to ponder if this may occur in GDM women.…”
Section: Introductionmentioning
confidence: 99%